Preferences of newborn mice for odours indicating closer genetic relatedness: is experience necessary? - Todrank, Josephine (The Royal Society, 2005)
Evidence from studies with adult rodents indicates that individual recognition enables distinctions between familiar individuals irrespective of relatedness (but including close kin) and a separate mechanism enables discriminations based on genetic relatedness without prior familiarity. For example, adult mice could assess the extent of their genetic relatedness to unfamiliar individuals using perceptual similarities between their individual odours. The ontogeny of this genetic relatedness assessment mechanism, however, had not been investigated. Here, in two-choice tests, newborn mice differentially preferred odours of more genetically similar lactating females (paternal aunts to unrelated conspecific and conspecific to heterospecific) even without prior direct exposure to adults with the tested genotypes. The results provide a direct demonstration of genetic relatedness assessment abilities in newborns and show that experience with parental odours is not necessary for genetic relatedness distinctions. Future studies will be necessary to determine whether exposure to odours of other foetuses in the womb or littermates shortly after birth affects this genetic relatedness assessment process.